MicroRNAs as biomarkers in chronic kidney disease. Issue 6 (November 2017) - Wonnacott, Alexa; Bowen, Timothy; Fraser, Donald J.
Abstract : Purpose of review: This review summarizes recent data supporting the concept that urinary microRNAs are a useful new class of biomarker. They may improve capacity to stratify patients with chronic kidney disease according to risk of progression, and may also inform about response to therapy. Recent findings: MicroRNAs are present, stable and readily quantifiable in tissues and body fluids, including urine, and have widespread importance as regulators in the kidney. Urinary microRNAs are typically released from the nephron or downstream structures, and their abundance may reflect altered microRNA expression in the kidney, or release into the lumen by the cells comprising the different regions of the nephron. As a consequence, abundance of specific microRNAs in the urine may change in various pathological states. Large-scale studies are now needed, to test the capacity of specific microRNAs to inform about risk and response to therapy. Summary: Urinary microRNAs appear useful sentinels for pathological processes occurring in the kidney and may enable a 'personalized medicine' approach to the management and stratification of renal disease.